Increased active sites and their accessibility of a N-doped carbon nanotube carbocatalyst with remarkably enhanced catalytic performance in direct dehydrogenation of ethylbenzene1. Issue 65 (16th July 2015) - Zhao, Zhongkui; Dai, Yitao; Ge, Guifang; Guo, Xinwen; Wang, Guiru
<x xml:space="preserve">Abstract</x> This work presents a facile, low-cost, but efficient strategy for synthesizing HN-CNTs with enlarged active sites and their accessibility to reactants for the direct dehydrogenation of ethylbenzene.